Analysis of workers’ perception for enhancing on-site safety climate in small-sized construction enterprises in South Korea - Yu, Chaeyeon; Gim, Wonsik; Jeong, Hojeong; Kim, Sungjin (Edelweiss Applied Science and Technology, 2025)
The construction industry is labor-intensive and exhibits a higher fatality rate compared to other sectors. Small to medium-sized construction sites often lack systematic safety management, highlighting the need for enhanced safety measures. Previous studies suggest that, due to the characteristics of these sites, deploying smart technologies presents challenges, making safety education a more feasible approach. This study reorganized existing literature to explore safety factors and the local atmosphere, creating survey questions based on research applied to general sites. A survey was conducted with 59 workers at small- to medium-sized construction sites in Korea, categorized into workers, skilled laborers, and managers. Independent variables (safety factors) and dependent variables (safety climate) were analyzed using bivariate correlation and multiple regression analysis. The results indicated that the emphasis on safety awareness varies depending on the role—worker, skilled laborer, or manager. This study aims to contribute to the effective improvement of safety standards at small construction companies by proposing practical safety management measures.